2012
DOI: 10.1016/j.jhep.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus (HCV) protein expression enhances hepatic fibrosis in HCV transgenic mice exposed to a fibrogenic agent

Abstract: electronic word count: 244 *Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
(51 reference statements)
1
10
1
Order By: Relevance
“…Thus, HCV infection of HSCs does not play a role in liver fibrosis. These results do not rule out a direct role of HCV infection of hepatocytes in the fibrogenic process as we recently suggested 17. Nevertheless, chronic inflammation in relation to the local immune response still appears to be the main trigger of liver fibrosis in patients with chronic hepatitis C.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Thus, HCV infection of HSCs does not play a role in liver fibrosis. These results do not rule out a direct role of HCV infection of hepatocytes in the fibrogenic process as we recently suggested 17. Nevertheless, chronic inflammation in relation to the local immune response still appears to be the main trigger of liver fibrosis in patients with chronic hepatitis C.…”
Section: Discussioncontrasting
confidence: 63%
“…Cellular proteins were processed as previously described 17. Cultured cells were lysed in cold lysis buffer containing 1% NP40, 10% glycerol, 100 mM Tris pH8, 100 mM KCl, protease and phosphatase inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…ROS is a critical regulator of hepatic fibrosis progression [60], [61], [62], [63], [64], whose level is increased by ethanol metabolism and HCV infection [60], [65], [66], [67]. It is also reported that HIV-1 and HCV cooperatively promotes hepatic fibrogenesis by inducing ROS [13], [68], and therefore we investigated whether Nef is a responsible element in generation of ROS in the hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…HCV core protein promotes HSCs proliferation, while the NS3 protease is pro-inflammatory by inducing transforming growth factor beta (TGF-β) signaling and collagen production in hepatic cells 18, 19 . Transgenic mice expressing the full-length HCV open reading frame in hepatocytes contributes to the development of hepatic fibrosis in the presence of carbon tetrachloride 20 . HCV subgenome replicon cells release TGF-β1 and other unidentified factors to induce procollagen gene expression in HSCs 21 .…”
Section: Introductionmentioning
confidence: 99%